Influence of ionic liquids on the syntheses and structures of Mn(ii) coordination polymers based on multidentate N-heterocyclic aromatic ligands and bridging carboxylate ligands. Issue 40 (22nd September 2015) - Qin, Jian-Hua; Wang, Hua-Rui; Pan, Qi; Zang, Shuang-Quan; Hou, Hongwei; Fan, Yaoting
Abstract : [RMI]Br probably serves as a template directing agent for the formation of a cluster helicate in2, while it serves as a mineralizing agent in3–6 . Additionally, [RMI]Br could obviously improve the crystal yield of7 . Abstract : Seven Mn(ii ) coordination polymers, namely [Mn2 (ptptp)Cl2 (H2 O)3 ]·H2 O n (1 ), [Mn(μ-ptptp)3 ]2 [Mn3 (μ3 -Cl)]2 ·2Cl·16H2 O (2 ), [Mn2 (ptptp)(ip)2 (H2 O)3 ]·H2 O n (3 ), [Mn2 (ptptp)(5-CH3 -ip)2 (H2 O)3 ]·H2 O n (4 ), [Mn4 (ptptp)(5-Br-ip)3 (H2 O)3 ]·4H2 O n (5 ), [Mn2 (ptptp)(Hbtc)(H2 O)2 ]·2H2 O n (6 ) and [Mn2 (ptptp)(tdc)(H2 O)2 ]·1.5H2 O n (7 ), have been prepared based on multidentate N-heterocyclic aromatic ligands and bridging carboxylate ligands (H2 ptptp = 2-(5-6-[5-(pyrazin-2-yl)-1 H -1, 2, 4-triazol-3-yl]pyridin-2-yl-1 H -1, 2, 4-triazol-3-yl)pyrazine; R-isophthalic acids, H2 ip-R: R = –H (3 ), –CH3 (4 ), –Br (5 ); H3 btc = trimesic acid (6 ); H2 tdc = thiophene-2, 5-dicarboxylic acid (7 )), in order to further probe the multiple roles of [RMI]Br ionic liquids in the hydro/solvothermal synthesis (RMI = 1-alkyl-3-methylimidazolium, R = ethyl, or propyl, or butyl). The successful syntheses of complexes2–6 suggest that in hydro/solvothermal synthesis the addition of a small amount of [RMI]Br plays a crucial role. Complex1 exhibits single right-handed helices constructed by ptptp ligands and Mn(ii ) ions. Complex2 possesses octanuclear helicate structures in which two propeller-shaped [Mn(μ-ptptp)3 ] 4− units embrace two [Mn3 (μ3 -Cl)] 5+ cluster cores inside. Complexes3 and4 are isostructural and display a 1D double chain formed by two kinds of pseudo meso-helices: (Mn-ptptp) n and (Mn-5-R-ip) n . Complex5 has a 2D structure containing 1D Mn(ii ) ion chains formed through carboxylates and [ptptp] 2− - N, N bridges. Complex6 shows a 2D structure formed by a meso-helix (Mn-ptptp) n and the partly deprotonated Hbtc ligands. Complex7 features a heterochiral [2 + 2] coaxially nested double-helical column formed by using the outer double-helices (Mn-ptptp) n as a template to encapsulate the inner double-helices (Mn-tdc) n with opposite orientation. All complexes were characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis, single-crystal X-ray crystallography and powder X-ray diffraction. The magnetic properties of1–7 were also investigated.